The pollen grains characteristics of Juglans L. species (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
The results of the detail analysis ofpollen grain features of 16 Juglansspecies confirmed the importance of these features for taxonomy, mainly at the section level. Morphological features of pollen grains of each species derived from different habitats (both cultivated in Ukraine and ones from natural habitats) are compared for the first time.
Keywords: pollen morphology, Juglans, diagnostic characters.